Solar energy engineering : processes and systems - Kalogirou, Soteris A. (Elsevier/Academic Press, 2014)
Provides a comprehensive guide to all areas of solar energy engineering from the fundamentals to the highest level of current research. Among the topics covered are solar collectors, solar water heating, solar space heating and cooling, industrial process heat, solar desalination, photovoltaic technology, solar thermal power systems, modeling of solar energy systems, and wind energy systems.
First edition 2009.
Keywords: Solar energy.; elektronické knihy; electronic books